Analysis of the chronic wound microbiota of 2, 963 patients by 16S rDNA pyrosequencing. Issue 1 (10th December 2015) - Wolcott, Randall D.; Hanson, John D.; Rees, Eric J.; Koenig, Lawrence D.; Phillips, Caleb D.; Wolcott, Richard A.; Cox, Stephen B.; White, Jennifer S.
Abstract: The extent to which microorganisms impair wound healing is an ongoing controversy in the management of chronic wounds. Because the high diversity and extreme variability of the microbiota between individual chronic wounds lead to inconsistent findings in small cohort studies, evaluation of a large number of chronic wounds using identical sequencing and bioinformatics methods is necessary for clinicians to be able to select appropriate empiric therapies. In this study, we utilized 16S rDNA pyrosequencing to analyze the composition of the bacterial communities present in samples obtained from patients with chronic diabetic foot ulcers ( N  = 910), venous leg ulcers ( N  = 916), decubitus ulcers ( N  = 767), and nonhealing surgical wounds ( N  = 370). The wound samples contained a high proportion of Staphylococcus and Pseudomonas species in 63 and 25% of all wounds, respectively; however, a high prevalence of anaerobic bacteria and bacteria traditionally considered commensalistic was also observed. Our results suggest that neither patient demographics nor wound type influenced the bacterial composition of the chronic wound microbiome. Collectively, these findings indicate that empiric antibiotic selection need not be based on nor altered for wound type. Furthermore, the results provide a much clearer understanding of chronic wound microbiota in general; clinical application of this new knowledge over time may help in its translation to improved wound healing outcomes.